Оценка эффективности разрушения горных пород алмазными поликристаличискими композиционными материалами при бурении - Закора, А.П.; Богданов, Р.К.; Исонкин, А.М.; Шульженко, А.А.; Гаргин, В.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
In this paper a detail investigation is presented for estimating the rock cutting efficiency of the drilling bits equipped with Tvesal and PDCM (AПKM) inserts. The relationship has been established between roughness parameters of a bottom hole and the mechanical drilling speed.